CXCL12, CA15-3, and Liver function Tests as Predictors of Liver Metastasis in Breast Cancer - A. Altimmime, Baqer; A. Rashid, Farah; Saady Raof, Yaala; Mansour, Omran (Al-Nahrain Journal of Science, 2025)
Breast cancer liver metastasis (BCLM) is a multi- step process that characterized by the spread of breast cancer cells to the liver. The majority of breast cancer-related deaths are due to metastatic rather than primary breast tumors. CXCL12 is one of the chemokines, small proteins capable of migrating various types of immune cells to the site of inflammation. CXCL12 can affect several cell biological activities, such as migration and proliferation, when it binds to its receptors.  The aim of this study is to investigate the predictive value of plasma CXCL12, CA15-3, and some liver-related parameter levels in breast cancer patients with liver metastasis. This study involves 94 women, 25 healthy controls and 69 patients with breast cancer, divided into three subgroups: 26 newly diagnosed women with primary breast cancer, 28 women with non-metastatic breast cancer undergoing chemotherapy, and 15 women with liver metastatic breast cancer. Plasma levels of CXCL12, CA15-3, albumin, ALP, ALT, and AST were measured using absorbance photometry and ELISA assays. The results of the study reveals that the level distributions of CXCL12 (p‎>0.9999) and CA15-3 (p‎>0.9999) showed no significant difference between breast cancer patients with and without liver metastasis. Albumin levels were significantly lower (‎‎p=0.0089) in women with liver metastatic breast cancer compared to those without metastasis. Levels of ALP‎ (p=‎0.0006‎), ALT (‎p=0.0015), and AST (p‎‎